Sex Differences in Computed Tomography Coronary Stenosis Severity Versus Flow Impairment and Impact on Revascularization, Clinical Events and Health Care Costs: A FORECAST Substudy - Lavinia Gabara; Jonathan Hinton; Mohamed Kira; James Shambrook; Ausami Abbas; Sam Wilding; Jonathon A. Leipsic; Pamela S. Douglas; Nick Curzen (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The impact of sex‐related differences in coronary atheroma and flow impairment severity on clinical events and costs remains unclear. Methods and Results This is a secondary analysis of patients with stable coronary artery disease who underwent both coronary computed tomography angiography  and fractional flow reserve derived from computed tomography as part of the FORECAST (Fractional Flow Reserve Derived From Computed Tomography Coronary Angiography in the Assessment and Management of Stable Chest Pain) trial, investigating (1) the relationship between coronary stenosis severity on coronary computed tomography angiography and fractional flow reserve derived from computed tomography FFRCT by sex and (2) the association with revascularization, resource usage, and adverse clinical events. A total of 212 patients (64 female participants [32.1%]) and 1245 vessels were included. There was no significant sex difference in the frequencies of significant coronary artery disease (38.2% of women versus 51.3% of men; P=0.073), but female participants had significantly less coronary flow impairment, according to the presence of at least 1 fractional flow reserve derived from computed tomography≤0.8 (47.0% versus 71.5%; P=0.008). Female subjects underwent fewer revascularization procedures (23.5% versus 42.3%; P=0.014), less coronary artery bypass graft surgery (2.9% versus 13.1%; P=0.025) and were less likely to be on statin treatment (72.0% versus 84.7%; P=0.022) by 9‐month follow‐up. This resulted in lower overall health care costs for female participants compared with male counterparts (median total cost, £1276 versus £2051; P=0.014). In multivariable Cox analysis the presence of significant coronary artery disease (hazard ratio [HR], 2.91; 95% CI, 1.30–6.51) and having a positive fractional flow reserve derived from computed tomography (HR, 4.11; 95% CI, 1.15–14.69) were independent predictors of major adverse cardiovascular events at 9 months, whereas sex was not statistically significant (p=0.13). Conclusions There are significant sex differences in the anatomico‐functional assessment of coronary artery disease leading to differences in clinical management, costs, and adverse events.